Parâmetros para formulação de uma política pública de segurança cidadã no Amazonas - Sette Júnior, Guilherme José (2019)
The present research sought to present the parameters that should guide the formulation of a public policy of Citizen Security in Amazonas. For this, a bibliographical research about the theoretical understanding of the violence, the concept of Citizen Security, the obstacles to Citizen Security and its strategies was carried out; documentary research in plans for coping with violence and in reports, in order to identify experiences that have succeeded in achieving effectiveness in offering good practices grounded in the concept of Citizen Security, being the Pacto Pela Vida Program of Pernambuco and the "Fica Vivo" General evidenced; data collection from IBGE, Human Development Atlas / UNDP, SISP (released by the Statistics Division of the Deputy Executive Secretariat for Intelligence - SEAI / SSP), the Mortality Information System (SIM) and the SEDUC database for the situational diagnosis of violence in Amazonas; and also consult the official websites of organizations of the state executive, for institutional survey. Finally, it was recommended, as parameters for formulating a public policy of Citizen Security in the Amazon, the need to construct a general and specific objective; definition of priority target audience, with ages ranging from 15 to 29 years, with low educational level and trajectory of involvement with crime; conducting dialogues with society; dialogues with public institutions; strategy formulation; preparatory actions; the implementation and execution with the Integrated Nucleus of Citizen Security and Prevention and with the programs, projects and actions; a system for measuring performance and results; and, finally, a management model for results.